Students’ acceptance of online rubric marking assessment in an Islāmic and Asian Civilizations Course at the Universiti Malaysia Pahang (UMP) - Aziman, Abdullah; Asar, Abdul Karim (International Islamic University of Malaysia (IIUM), 2020)
There are many tools available over the Internet providing educators with the platform to implement online rubric marking assessment (ORMA). However, only a few success stories and studies about its usage among Malaysian higher education institutions have been reported, particularly in general courses such as Islāmic and Asian Civilizations (“TITAS”). Hence, this study aims to investigate students’ acceptance of an online rubric marking assessment of TITAS course at Universiti Malaysia Pahang (UMP). The study is descriptive using a self-administered online survey which deployed through UMP's official learning management system (LMS). The participants comprised 152 students out of a population of 1,590 students who took the TITAS course in Semester II of the 2016/ 2017 session. The analysis shows that in general the students were ready and very positive towards the use of ORMA due to its effectiveness and impact on their learning. Although there were many challenges in implementing ORMA, generally it was worth implementing in transforming higher education in an effort to embrace Industrial Revolution 4.0.